Nasopharyngeal carcinoma in childhood - Bidasari Lubis; Nelly Rosdiana; Saur L Margaretha (Indonesian Pediatric Society, 2005)
Nasopharyngeal carcinoma (NPC) is a raretumor which originates from thenasopharyngeal epithelium. It accountsfor <1% of childhood malignancy cases,whereas almost all adult nasopharyngeal cancers arecarcinomas. In children, nasopharyngealmalignancies are mostly rhabdomyosarcomas andonly 20-30% are carcinomas or lymphomas.Approximately one third of the undifferentiated typeNPC is diagnosed in adolescents or young adults.